Transformation of Islamic Education: Journey of Islamic Education from Prophet to Umayyad and Abbasid - Irwan; Tobroni; Nurhakim (Tarbiyah Departement collaboration with AMCA, 2023)
This research examines the transformation of Islamic education from the time of the Prophet Muhammad to the Umayyad and Abbasid caliphs. This study explores the changes and developments in the system, curriculum, and methodology of Islamic education in that historical period. This study uses a qualitative type with a library research approach, analyzing primary and secondary sources, including Islamic texts, historical records, and scientific works. Data collection techniques were carried out through literature searches using online databases. Data analysis in this study was carried out by reading and understanding the contents of the relevant literature. The transformation of Islamic education from the time of the Prophet to the Umayyad and Abbasid Caliphates represented significant changes in educational approaches, curricula, and facilities. This development reflects the high appreciation of science, the dissemination of knowledge through bookstores and literary salons, as well as the critical role of the clergy as educators and intellectual leaders in Islamic society.